Effects of dietary Lactobacillus rhamnosus JCM1136 and Lactococcus lactis subsp. lactis JCM5805 on the growth, intestinal microbiota, morphology, immune response and disease resistance of juvenile Nile tilapia, Oreochromis niloticus. Issue 76 (May 2018) - Xia, Yun; Lu, Maixin; Chen, Gang; Cao, Jianmeng; Gao, Fengying; Wang, Miao; Liu, Zhigang; Zhang, Defeng; Zhu, Huaping; Yi, Mengmeng
Abstract: The present study aimed to evaluate the individual and combined effects of Lactobacillus rhamnosus (LR) JCM1136 and Lactococcus lactis subsp. lactis (LL) JCM5805 on the growth, intestinal microbiota, intestinal morphology, immune response and disease resistance of juvenile Nile tilapia ( Oreochromis niloticus ). A total of 720 apparently healthy juvenile Nile tilapia (0.20 ± 0.05 g) were randomly divided into four equal groups. Fish were fed with a basal diet (CK) supplemented with JCM1136 (LR), JCM5805 (LL), and JCM1136 + JCM5805 (LR+LL) at 1 × 10 8 CFU/g basal diet for 6 weeks, followed by a basal diet for 1 week. After 6 weeks of feeding, the LL treatment significantly increased the growth and feed utilization of Nile tilapia when compared with the CK. Light microscopy and transmission electron microscopy images of the midgut revealed that probiotic supplementation significantly increased gut microvilli length and microvilli density compared to CK. The transcript levels of several key immune-related genes in the mid-intestine and liver of fish were analyzed by means of quantitative polymerase chain reaction (qPCR) at the end of the sixth week. The results showed the following: when compared to CK group, fish in LR had significantly increased transcript levels of IFN-γ, lyzc, hsp70 and IL-1β in the intestine; LL fish showed significantly increased expressions of TNF-α, IFN-γ, lyzc, hsp70 and IL-1β in the intestine and liver; and intestine lyzc, hsp70 and IL-1β and liver TNF-α, IFN-γ, hsp70 and IL-1β were significantly increased in LR+LL fish. Following a 6-week period of being fed probiotics or a control diet, the tilapia were challenged with an intraperitoneal injection of 20 μl of the pathogenic Streptococcus agalactiae (WC1535) (1 × 10 5 CFU/ml). The survival rates of the probiotic-fed groups were significantly higher than that of the CK group, and the LL group had the highest survival rate. High-throughput sequencing revealed a significantly higher presence of JCM5805 in the guts of LL fish during the period of probiotic application, but this was no longer detected in all LL samples 1 week post cessation of probiotic administration. Cessation of probiotic administration led to disorders of individual gut microbes within the LR and LL groups. Statistical analysis (LEfSe) demonstrated that three phyla, namely, Bacteroidetes, Fusobacteria and Actinobacteria were enriched in the CK group, while the abundance of Proteobacteria was greater in the probiotic-fed fish. At the genus level, Plesiomonas, which includes potential pathogens of fish, were significantly decreased in the probiotic-fed groups. In contrast, a significant increase of Rhizobium and Achromobacter, which can produce a variety of enzymes with cellulolytic and pectolytic activity, were observed in fish fed with probiotics, indicating that dietary probiotics were helpful in the propagation of some probiotic bacteria. Our data revealed that JCM1136 and JCM5805, as a feed additive at 10 8 CFU/g feed, could improve intestinal morphology, enhance immune status and disease resistance, and affect the gut microbiota of tilapia; thus, these additives could be used as probiotics for juvenile Nile tilapia. JCM5805 was more effective than JCM1136 or the mixture of the two for promoting the growth, enhancing the immune status and disease resistance of tilapia. Highlights: JCM5805 increased the growth and feed utilization of Nile tilapia. Both of JCM1136 and JCM5805 improved intestinal health, immune status and Streptococcus agalactiae resistance in tilapia. JCM5805 was more effective than JCM1136 or the mixture of the two. JCM1136 and JCM5805 altered the intestinal microbiota of Nile tilapia. The JCM5805 could adhere to the intestinal mucosa for proliferating, but couldn't colonize in the intestine of tilapia.